Relative motion wave functions and spectroscopic factors in 5He dt d channel - Afanasyeva, N. V.; Burkova, N. A.; Zhaksybekova, K. A.; Kosanov, I. A. (Recent Contributions to Physics, 2013)
Within the two-body t-model for 7Li nucleus the relative motion wave functions in 5 He+d channel have been built by using the projecting method in the dynamic potential cluster model. It is necessary to note, that in this calculations the dt configuration of 5 He nucleus has been taken into account. The graphs of obtained 5 He +d relative motion wave functions at the various values of the oscillatory parameter of α- particle are presented. S-wave of the relative d5 He motion wave function, obtained in this work within the dt configuration of 5 He nucleus, doesn’t have a node in contrast to the corresponding one obtained earlier within the n configuration of 5 He nucleus. Obtained functions have been used for calculation of the spectroscopic Sd -factors of the deuteron separation from 7 Li nucleus. Also the comparative analysis of the obtained spectroscopic Sd-factors with corresponding ones calculated earlier within the n configuration of this nucleus has been performed.